Multimodal Communication A social semiotic approach to text and image in print and digital media - Wong, May.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
"This book makes a striking contribution combining Kress and van Leeuwen's social semiotic analysis with extensive and fascinating in-depth historical research to bring insights into a range of print and digital media showing how multimodality can be fruitfully adapted with the sensitivity to non Western media." - Professor David Machin, Department of Media and Communication, Örebro University, Sweden This book draws on visual data, ranging from advertisements to postage stamps to digital personal photography, to offer a complex interpretation of the different social functions realised by these texts as semiotic artefacts. Framed within the media environment of the city of Hong Kong, the study demonstrates the importance of social context to meaning making and social semiotic multimodal analysis. This book will be of interest to readers in the arts, humanities and social sciences, particularly within the fields of semiotics, visual studies, design studies, media and cultural studies, anthropology and sociology. May L-Y Wong is Adjunct Associate Professor in the School of English at The University of Hong Kong. Her research focusses on social-semiotic approaches to visual texts. In particular, she is interested in the relation between multimodality and culture, drawing on research in social semiotics to explain the utility of multimodal resources in various discursive contexts which are of significance to local cultural values and heritage.
Chapter 1: Social semiotics: setting the scene -- PART I: PRINT MEDIA -- Chapter 2: Slim arms, waist, thighs and hips, but not the breasts: portrayal of female body image in Hong Kong's magazine advertisements -- Chapter 3: Postage stamps as windows on social changes and identity in postcolonial Hong Kong -- PART II: DIGITAL MEDIA -- Chapter 4: Emotional branding in multimodal personal loan TV advertisements: analysing voices and engagement -- Chapter 5: The discourse of advertising for luxury residences in Hong Kong: a multimodal critical discourse analysis -- Chapter 6: Digital photography and identity of Hong Kong females: a case study of Facebook images -- Chapter 7: Significance of social semiotic research.
Keywords: Semiotics; Linguistics -- Methodology; Sociolinguistics; Communication; Ethnology -- Asia; Culture; Semiotics; Research Methods in Language and Linguistics; Sociolinguistics; Media and Communication; Asian Culture